Preditores da adaptação à Universidade: o papel da vinculação, desenvolvimento psicossocial e coping - Cabral, Joana (2010)
This study, with a sample of 387 freshmen, explores the influence of parental attachment, psychosocial development (assed on the beginning of the academic year) and coping strategies on adjustment to college (assed in end of this same year) using Structural Equations Models. It is argued that parental attachment influences adjustment to college by fostering the development of psychosocial competencies, such as autonomy, (sense of) identity, and coping responses. These competencies are, in turn, central to college adjustment processes. Results support the importance a secure quality of attachment to foster developmental processes, which, in turn, promote coping resources to face the demands faced of adjustment to college.